TERMINATION OF EMPLOYMENT DURING THE PROBATION PERIOD IN A FIXED TERM EMPLOYMENT AGREEMENT (PKWT)(Study of Case Decision No. 271/Pdt.Sus-PHI/2018/PN.Mdn) - Amir (Journal of Constitutional Principles, 2025)
There is no probationary period in PKWT. Law Number 13 concerning Manpower of 2003 states: The employment contract imposed does not require a probationary period. If a probationary period is required in the employment contract, the probationary period does not apply. Certain provisions of the Temporary Employment Contract (PKWT) and the reasons for the probationary period change to a Permanent Employment Contract (PKWTT), so that when they carry out Termination of Employment (PHK) they are entitled to a fixed salary.